Politics & gender. - American Political Science Association. Women and Politics Resear ch Section (New York, NY : Cambridge University Press for the Women and Polit ics Research Section of the American Political Science Association, 2005)
Publishes the scholarship on gender and politics and on women and po litics. It aims to represent the full range of questions, issues, and a pproaches on gender and women across the major subfields of political s cience, including comparative politics, international relations, politi cal theory, and U.S. politics.
Latest issue consulted: Vol. 9, no. 4 (December 2013)
Latest issue consulted: Vol. 4, no. 4 (Dec. 2008).
Keywords: Sex role -- Political aspects -- Periodicals; Women -- Political activity -- Periodicals